If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + 6 = 9m + -3 Reorder the terms: 6 + 6m = 9m + -3 Reorder the terms: 6 + 6m = -3 + 9m Solving 6 + 6m = -3 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. 6 + 6m + -9m = -3 + 9m + -9m Combine like terms: 6m + -9m = -3m 6 + -3m = -3 + 9m + -9m Combine like terms: 9m + -9m = 0 6 + -3m = -3 + 0 6 + -3m = -3 Add '-6' to each side of the equation. 6 + -6 + -3m = -3 + -6 Combine like terms: 6 + -6 = 0 0 + -3m = -3 + -6 -3m = -3 + -6 Combine like terms: -3 + -6 = -9 -3m = -9 Divide each side by '-3'. m = 3 Simplifying m = 3
| 2*-34= | | -93*12= | | 23x+3y=20 | | 9-102= | | -9x-6=10 | | 5m-8=13 | | Y=-3x-9 | | -2+x/2+6 | | -14580*-816= | | r+3r(r-6)=1 | | 2*-408= | | 5+2a=a+7 | | -4(x+2)+3(2x+3)=11 | | -14580+816= | | 80/120=x/2 | | x(1+9x)-9x=1 | | -8+6x=22 | | 6p+1=8-p | | y^3=8000 | | 4(7+5)/4 | | 2*408= | | -4=-4+8p-8p | | 7-8x=5x+18 | | 4k-3=17-k | | -1215*12= | | 70+x+10=180 | | 4(a-7)+14=2(a-6) | | 7n-2=4n+7 | | 4y+3=y+15 | | 8(x-9)-8=1 | | 9-1224= | | -4(-5b-7)=-92 |